UNA NUEVA ESPECIE DE TRICONODONTA (MAMMALIA), DE LA FORMACION LOS ALAMITOS, PROVINCIA DE RIO NEGRO y COMENTARIOS SOBRE SU FAUNA DE MAMIFEROS (Ameghiniana, 2013)
A new species of the triconodont genus Austrotriconodon from the Los Alamitos Formation is described and discussed. It is based on a lower left molar. the last lower premolar and an upper right molar. The new species A. sepulvedai is twice the size of the type species A. mckennai. The distinctive characters of both the lower and upper molars of Austrotriconodon suggests that it belongs to a new family. Austrotriconodontidae nov. characterized by upper molars with cusps in palisade, with the B cusp bigger than the A cusp. A new list of the mammalian taxa from Los Alamitos is given, and new interpretations of the systematics of these taxa are discussed. Vertebrate-Ages, used for the continental vertebrate assemblages of Los Alamitos and Río Colorado Formations are here proposed as useful time units to define biochronology for the sequence of Cretaceous terrestrial assemblages from Argentina.